2012
DOI: 10.1039/c2ob25595b
|View full text |Cite
|
Sign up to set email alerts
|

The Rabe amination after a century: direct addition of N-heterocycles to carbonyl compounds

Abstract: A catalytic version of the Rabe electrophilic amination is presented. This kind of reaction was originally employed in 1918 in a key step for the conversion of quinotoxine to quinine. Ketones and α-substituted aldehydes give the corresponding α-aminated carbonyl compounds in moderate yield. α,α-Unsubstituted aldehydes give rise to amino ketones via a novel rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Interestingly, the majority of these approaches utilize electrophilic sources of nitrogen, primarily azodicarboxylates and organonitroso compounds, with subsequent derivatization of the amine functionality (Scheme a) . While alternative entries into enantioenriched α-amino carbonyl compounds have been described, highly enantioselective nucleophilic amination reactions remain illusive . A nucleophilic approach would allow for a broader scope of amine functionalization, potentially permitting incorporation of moieties, such as arylamines, that are challenging to access through electrophilic additions (Scheme b).…”
mentioning
confidence: 99%
“…Interestingly, the majority of these approaches utilize electrophilic sources of nitrogen, primarily azodicarboxylates and organonitroso compounds, with subsequent derivatization of the amine functionality (Scheme a) . While alternative entries into enantioenriched α-amino carbonyl compounds have been described, highly enantioselective nucleophilic amination reactions remain illusive . A nucleophilic approach would allow for a broader scope of amine functionalization, potentially permitting incorporation of moieties, such as arylamines, that are challenging to access through electrophilic additions (Scheme b).…”
mentioning
confidence: 99%
“…The alterative pathway to GB 13 can lead to himgaline via another Michael addition or GB 16 when R is a leaving group such as a halogen (X) via a Rabe amination. , Aromatization of ring B then leads to GB 22, which can be acetylated to the new alkaloid GB 30 ( 4 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…elevated reaction temperatures for substrates containing electron-rich π-systems (34), or the addition of Lewis acids for aliphatic ketones to facilitate the enolization event (36), enabled the successful conversion of otherwise challenging substrates. The utility and generality of the procedure was demonstrated with substrates usually susceptible to 1,2-elimination events (35), and the one-step synthesis of the appetite suppressant amfepramone in 80% yield, which is comparable Guo's peroxide-mediated synthesis (72%). In 2014, Huang and co-workers showed that the use of a non-commercial dimethyl-Pybox ligand with MacMillan's conditions marginally increased the yields for comparable substrates.…”
Section: Rickmentioning
confidence: 94%
“…As the gene-ration of these starting materials has significant drawbacks, such as increased step count and the handling of toxic and corrosive bromine, it is desirable to achieve direct amination of cheap and readily available ketones within a single synthetic operation. Examples of direct aminations were independently developed by Bella 35 and Liang 36 in 2012. Bella used electrophilic N-chloropyrrolidine and N-chloropiperidine to obtain the amino ketones in 22-63% yield, with the pyrrolidine or piperidine unit incorporated in the final product.…”
Section: Ketonesmentioning
confidence: 99%